Determinantes de la inclusión financiera desde un enfoque de ka demanda en Riobamba para el año 2022. - Granizo Montaño, Jairo Gonzalo (2023)
His study aims to examine, from a microeconomic perspective, the determinants of financial inclusion in the Riobamba canton of the province of Chimborazo, during the year 2022. Financial inclusion plays a crucial role in economic growth and the well-being of the population and contributes to reducing economic inequality. The focus is on the demand for access to the financial system, due to the scarcity of information and data available in this area at the location in question. Information needed for this study will be collected through surveys of canton residents in urban and rural areas. The collected data will be analyzed using logit and probit econometric models, and the results of the best model will be evaluated using goodness-of-fit measures, such as the confounding matrix and the ROC curve. The results of the analysis indicate that the most significant factors that determine access to the financial system are income, educational level, and formal employment, which positively influence the five inclusion indicators selected for the study. In addition, it was discovered that financial inclusion is directly related to the level of income and education of people, so having a high level of these variables increases the probability of being part of the financial system. Finally, it was found that having stable employment and internet access also contribute positively to financial inclusion